2013
DOI: 10.1055/s-0033-1343427
|View full text |Cite
|
Sign up to set email alerts
|

Operative Genitalangleichung bei Mann-zu-Frau-Transsexualität: Gibt es Leitlinien oder Standards?

Abstract: Zusammenfassung Hintergrund: Seit 2011 liegen die ?Standards of Care? zur Diagnostik und Behandlung von Transsexuellen von der WPATH (World Professional Association for Transgender Health) in der erweiterten siebten Version vor. Nachdem auch in den letzten Jahren mehrere ?bersichtsarbeiten auf dem Gebiet der genitalen Geschlechtsangleichung erschienen sind, soll untersucht werden, ob f?r das operative Vorgehen der genitalen Geschlechtsangleichung bei Mann-zu-Frau-Transsexuellen evidenzbasierte Leitlinien oder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 6 publications
0
4
0
1
Order By: Relevance
“…A detailed sexual history is thus of utmost importance during the preoperative assessment and physical exam of new patients presenting for GAS. An interdisciplinary approach with psychiatrists and endocrinologists is not only recommended but—in Germany—even mandated to obtain treatment coverage by public and private insurers 32 …”
Section: Discussionmentioning
confidence: 99%
“…A detailed sexual history is thus of utmost importance during the preoperative assessment and physical exam of new patients presenting for GAS. An interdisciplinary approach with psychiatrists and endocrinologists is not only recommended but—in Germany—even mandated to obtain treatment coverage by public and private insurers 32 …”
Section: Discussionmentioning
confidence: 99%
“…According to Sohn, Hatzinger, & Wirsam (2013), 80% subjective satisfaction rate can be expected following gender reassignment surgery. Löwenberg et al (2010) reported 92% general satisfaction after SRS.…”
Section: Discussionmentioning
confidence: 99%
“…Den Abschluss bildete ein Gast aus der Urologie -Prof. Michael Sohn aus Frankfurt a. M. diskutierte die Frage: "Operative Genitalangleichung bei Mann-zu-Frau-Transsexualität -Gibt es Leitlinien oder Standards?" [7]. Die Sitzung war sehr gut besucht und die Black Box im Gasteig hatte einen ganz besonderen Charme.…”
Section: Hamipla Best Paper Sitzung Bei Der Dgpräc Jahrestagung In Müunclassified